Progress in the study of the correlation between sepsis and intestinal microecology - Tao, Yan-Lin; Wang, Jing-Ran; Liu, Miao; Liu, Ya-Nan; Zhang, Jin-Qiu; Zhou, Yi-Jing; Li, Shao-wei; Zhu, Shu-Fen (Frontiers in Cellular and Infection Microbiology, 2024)
Sepsis, a disease with high incidence, mortality, and treatment costs, has a complex interaction with the gut microbiota. With advances in high-throughput sequencing technology, the relationship between sepsis and intestinal dysbiosis has become a new research focus. However, owing to the intricate interplay between critical illness and clinical interventions, it is challenging to establish a causal relationship between sepsis and intestinal microbiota imbalance. In this review, the correlation between intestinal microecology and sepsis was summarized, and new therapies for sepsis intervention based on microecological target therapy were proposed, and the shortcomings of bacterial selection and application timing in clinical practice were addressed. In conclusion, current studies on metabolomics, genomics and other aspects aimed at continuously discovering potential probiotics are all providing theoretical basis for restoring intestinal flora homeostasis for subsequent treatment of sepsis.